Contribution of alcohol to deaths in road traffic accidents in Tayside 1982-6. Issue 6634 (21st May 1988) - Foster, Graham R; Dunbar, James A; Whittet, David; Fernando, Gyan C A
Abstract : In Britain the precise number and relative proportions of deaths among drivers, passengers, and pedestrians in road traffic accidents related to alcohol are not known. These data were obtained in Tayside by cross matching police accident records with blood alcohol concentrations at necropsy. Of 71 alcohol-related deaths 30 were the drivers (or motorcyclists) themselves, nine were their passengers, 23 were pedestrians with raised blood alcohol concentrations, and nine were innocent victims. The high blood alcohol concentrations of the intoxicated drivers, passengers, and pedestrians, which may point to alcoholism, suggest that publicity campaigns will be of little value in reducing the number of deaths in road traffic accidents related to alcohol. The time at which these accidents occurred was related to licensing hours, and this should be taken into account when considering changes in licensing laws.